2012
DOI: 10.3899/jrheum.120079
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100A8/A9, But Not Follistatin-like Protein 1 and Interleukin 18, May Be a Useful Biomarker of Disease Activity in Adult-onset Still’s Disease

Abstract: The data suggest that serum S100A8/A9 may be a useful biomarker for evaluating disease activity in patients with AOSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 35 publications
5
55
1
3
Order By: Relevance
“…Increased serum levels of this molecule were found in patients with AOSD, in close correlation with disease activity and severity. Later on, such results were confirmed and a positive correlation of S100A8/A9 with leukocyte count, ESR, CRP, ferritin, systemic disease score and also a decrease after disease activity status resolution were detected [85]. More recently, a correlation with disease activity, serological markers (ESR, CRP, ferritin) and systemic score was described for the S100A12 protein too [86].…”
Section: S100a8 A9 A12mentioning
confidence: 84%
See 1 more Smart Citation
“…Increased serum levels of this molecule were found in patients with AOSD, in close correlation with disease activity and severity. Later on, such results were confirmed and a positive correlation of S100A8/A9 with leukocyte count, ESR, CRP, ferritin, systemic disease score and also a decrease after disease activity status resolution were detected [85]. More recently, a correlation with disease activity, serological markers (ESR, CRP, ferritin) and systemic score was described for the S100A12 protein too [86].…”
Section: S100a8 A9 A12mentioning
confidence: 84%
“…[60] S100A8/A9 11,770 ± 8840 ng/ml 36 [85] 57.11 ± 25.38 ng/ml 25 [84] 0.5-9 ng/ml 18 [35] S100A12 547.9 ± 148.4 ng/ml 37 [86] Procalcitonin 0.09-71 ng/ml 5 [70] 2-10 ng/ml 1 [72] 0-1.4 ng/ml 38 [73] SD: Standard deviations.…”
Section: Biomarkersmentioning
confidence: 99%
“…Some studies showed that systemic juvenile idiopathic arthritis (systemic JIA) is associated with high concentrations of S100A8/A9 [17,18,19]. Furthermore, we showed previously elevated serum S100A8/A9 levels in AOSD patients, compared with healthy controls (HCs), and their correlation with several disease activity markers in AOSD [20]. …”
Section: Introductionmentioning
confidence: 84%
“…S100A8/A9 has shown to be a biomarker of several inflammatory diseases including RA, systemic JIA, inflammatory bowel disease, and AOSD [19,20,22,23,24]. One study showed that serum S100A8/A9 levels were higher in patients with active systemic JIA, compared with those with systemic infections and HCs [18].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the calcium-binding proteins S100A8, S100A9, and IL-18 on 36 patients with AOSD, S100A8/A9 levels were higher than in patients with rheumatoid arthritis or healthy controls, correlated with known inflammatory markers and disease activity scores, and significantly decreased after treatment of AOSD. IL-18 levels performed even better for diagnosis, with a sensitivity of 91.7% and a specificity of 99.1% at a cutoff of 366.1 pg/mL, but did not decrease after treatment of AOSD 35. Finally, in a study of 30 patients with AOSD and age-matched controls, mean calprotectin levels were significantly higher (61 ng/ml vs 35 ng/ml, P <0.05) and levels decreased after treatment of AOSD 36.…”
Section: Future Prospects In Diagnostic Biomarkersmentioning
confidence: 94%